Fabrication of Functional Polymers with Gradual Release of a Bioactive Precursor for Agricultural Applications - Martin-Trasancos, R; Martin-Trasancos, R (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Biodegradable and biocompatible polymeric materials and stimulus-responsive hydrogels are widely used in the pharmaceutical, agricultural, biomedical, and consumer sectors. The effectiveness of these formulations depends significantly on the appropriate selection of polymer support. Through chemical or enzymatic hydrolysis, these materials can gradually release bioactive agents, enabling controlled drug release. The objective of this work is to synthesize, characterize, and apply two controlled-release polymeric systems, focusing on the release of a phyto-pharmaceutical agent (herbicide) at varying pH levels. The copolymers were synthesized via free radical polymerization in solution, utilizing tetrahydrofuran (THF) as the organic solvent and benzoyl peroxide (BPO) as the initiator, without the use of a cross-linking agent. Initially, the herbicide was grafted onto the polymeric chains, and its release was subsequently tested across different pH environments in a heterogeneous phase using an ultrafiltration (UF) system. The development of these two controlled-release polymer systems aimed to measure the herbicide’s release across different pH levels. The goal is to adapt these materials for agricultural use, enhancing soil quality and promoting efficient water usage in farming practices. The results indicate that the release of the herbicide from the conjugate systems exceeded 90% of the bioactive compound after 8 days at pH 10 for both systems. Furthermore, the two polymeric systems demonstrated first-order kinetics for herbicide release in aqueous solutions at different pH levels. The kinetic constant was found to be higher at pH 7 and 10 compared to pH 3. These synthetic hydrogels are recognized as functional polymers suitable for the sustained release of herbicides in agricultural applications. © 2025 by the authors.